Occupational regulation, institutions, and migrants' labor market outcomes - Maria Koumenta; Mario Pagliero; Davud Rostam-Afschar (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2022)
We study how licensing, certification and unionisation affect the wages of natives and migrants and their representation among licensed, certified, and unionized workers. We provide evidence of a dual role of labor market institutions, which both screen workers based on unobservable characteristics and also provide them with wage setting power. Labor market institutions confer significant wage premia to native workers (3.9, 1.6, and 2.7 log points for licensing, certification, and unionization respectively), due to screening and wage setting power. Wage premia are significantly larger for licensed and certified migrants (10.2 and 6.6 log points), reflecting a more intense screening of migrant than native workers. The representation of migrants among licensed (but not certified or unionized) workers is 14% lower than that of natives. This implies a more intense screening of migrants by licensing institutions than by certification and unionization.
urn:nbn:de:bsz:100-opus-20166
Keywords: J61; J31; J44; J71; J16; 330; Arbeitsmarkt; Lohn; Zuwanderung; Occupational; regulation; Licensing; Certification; Unionization; Migration; Wages